2021
DOI: 10.52711/2349-2996.2021.00090
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Midwifery Students’ Attitudes Towards Research: A Descriptive Study

Abstract: Background: Some studies found that nurses are not actively involved in research. To address this issue, it is important to investigate the structure of training that nurses got while at school of nursing. To promote evidence-based practice, nursing and midwifery students must be actively involved in research. Several studies have reported on the attitude of nursing students towards research in different countries. However, no study has assessed attitude of both nursing and midwifery students towards research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Similar findings were found in the study by Amoo and Gbadamosi, where only 37% of participants said they enjoyed conducting research since many of them thought it was stressful, challenging, and about a complex subject [ 39 ]. There is a need to reinforce postgraduate nursing research education as it can positively affect nurses’ attitudes toward nursing research, resulting in better patient treatment and care.…”
Section: Resultssupporting
confidence: 84%
“…Similar findings were found in the study by Amoo and Gbadamosi, where only 37% of participants said they enjoyed conducting research since many of them thought it was stressful, challenging, and about a complex subject [ 39 ]. There is a need to reinforce postgraduate nursing research education as it can positively affect nurses’ attitudes toward nursing research, resulting in better patient treatment and care.…”
Section: Resultssupporting
confidence: 84%
“…In studies conducted with nursing students, it was found that students' anxiety toward conducting research was moderate (Kes & Şahin, 2019) or high (Gerçek et al, 2016;Güleç & Saruhan, 2013). In most of these studies, more than half of the participants affirmed that conducting research made them nervous, anxious and scared (Amoo & Gbadamosi, 2021;Muzzmal et al, 2018). In this study, students got an average score of 23.92 ± 9.29 on the anxiety scale.…”
Section: Discussionmentioning
confidence: 99%